Madrasah Nidzamiyah (Latar Belakang, Profil, Kurikulum Dan Metode Pendidikannya) - Muhammad Sholeh (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2017)
Nidzhamiyah Madrasah is an educational institution founded by Nidzham al-Mulk, a vizier during the time of the Abbasid Daula. The institute was first established in Nishapur. This educational institution was established to stem the Shi'ites. Nizhamiyah madrasah educational institution is one of the forerunners of modern Islamic educational institutions both in terms of curriculum, teaching methods, facilities and infrastructure, administration and financing. The curriculum focuses on the Qur'an, Arabic literature, the history of the Prophet, and numeracy. His teaching system focuses on the Shafi'i school and Ash'ariyyah. However, in the curriculum used there is a proportional balance between religious disciplines (tafseer, hadith, jurisprudence, kalam, and others) and aqliyah disciplines (philosophy, logic, mathematics, medicine, etc.).